Evaluasi Penerapan Sertifikat Laik Fungsi Sebagai Instrumen Tata Kelola Bangunan di Kota Semarang - Marina, Transiska Luis (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
This study evaluates the impact of green building policies on sustainable development in Semarang City, focusing on the issuance of Building Feasibility Certificates (SLF) from 2020 to 2024. Descriptive statistics, temporal trends, and geographic distribution analyses were employed to examine SLF issuance patterns, distribution across districts, and the policy’s effectiveness in promoting environmental sustainability. Results indicate positive contributions of SLF policies to environmental sustainability, particularly in improving energy efficiency and resource conservation, despite challenges like limited public awareness and weak inter-agency coordination. Recommendations include enhancing policy dissemination, strengthening cross-sectoral collaboration, and improving local technical capacities to ensure all buildings comply with sustainability standards. This study offers valuable insights to support sustainable urban development and strategic guidance for policymakers in achieving global sustainability goals.